The role of matrix rhythm therapy in managing and breaking tissue adhesions - Rizvi, Arif; Asthana, Sumit; Naqvi, Zia Abbas; Fatima, Tahzeeb (International Journal of Research in Orthopaedics, 2025)
This article explores the potential of Matrix Rhythm Therapy (MRT) in addressing tissue adhesions, focusing on its relevance as a non-invasive and effective treatment modality. A systematic review of current literature was conducted using databases such as PubMed, Scopus, and Web of Science. Search terms included "Matrix Rhythm Therapy," "tissue adhesions," "non-invasive treatments," and "mobility improvement." MRT demonstrates promising results in breaking tissue adhesions, improving mobility, and reducing pain by restoring cell matrix dynamics and tissue elasticity. MRT represents a viable adjunct or alternative to conventional treatments for tissue adhesions. Further research is required to standardize protocols and validate its efficacy across diverse clinical scenarios.